Hydrogen-Bond Free Energy of Local Biological Water - Park, Won Woo; Lee, Kyung Min; Lee, Byeong Sung; Kim, Young Jae; Joo, Se Hun; Kwak, Sang Kyu; Yoo, Tae Hyeon; Kwon, Oh Hoon (Angewandte Chemie - International Edition, 2020)
Here, we propose an experimental methodology based on femtosecond-resolved fluorescence spectroscopy to measure the hydrogen (H)-bond free energy of water at protein surfaces under isothermal conditions. A demonstration was conducted by installing a non-canonical isostere of tryptophan (7-azatryptophan) at the surface of a coiled-coil protein to exploit the photoinduced proton transfer of its chromophoric moiety, 7-azaindole. The H-bond free energy of this biological water was evaluated by comparing the rates of proton transfer, sensitive to the hydration environment, at the protein surface and in bulk water, and it was found to be higher than that of bulk water by 0.4 kcal mol−1. The free-energy difference is dominated by the entropic cost in the H-bond network among water molecules at the hydrophilic and charged protein surface. Our study opens a door to accessing the energetics and dynamics of local biological water to give insight into its roles in protein structure and function.
Keywords: Biological water; Chromophoric moieties; Coiled-coil proteins; Experimental methodology; Femtochemistry; Free-energy difference; Isothermal conditions; Protein engineering; Density Functional Theory; Hydrogen Bonding; Molecular Structure; Proteins; Protons; Spectrometry, Fluorescence; Surface Properties; Thermodynamics; Water; biological water; femtochemistry; hydrogen-bond free energy; protein engineering; proton transfer